2016
DOI: 10.1155/2016/3939685
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Schwannoma of Parotid Gland: Difficulties in Diagnosis and Management

Abstract: Facial nerve schwannomas (FNS) are encapsulated benign tumors arising from Schwann cells of seventh cranial nerve. Most of the facial nerve schwannomas are localized in intratemporal region; only 9% of cases involve a portion of the extratemporal segment. Preoperative diagnosis is often unclear; diagnosis is often made intraoperatively. Management of intraparotid FNS is troublesome because of the facial nerve paralysis. In this report we presented a case of intraparotid schwannoma in a 55-year-old male patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Cho et al overcame this difficulty by employing intra--operative frozen section studies to reach the correct diagnosis [26]. On the one hand, frozen section examination that has been performed intra--operatively is recommended for both diagnosis and exclusion of malignancy [5,27]. On the other hand, occasionally the schwannoma is mistaken for a fibrosarcoma leading to unwarranted radical surgery [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al overcame this difficulty by employing intra--operative frozen section studies to reach the correct diagnosis [26]. On the one hand, frozen section examination that has been performed intra--operatively is recommended for both diagnosis and exclusion of malignancy [5,27]. On the other hand, occasionally the schwannoma is mistaken for a fibrosarcoma leading to unwarranted radical surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology is still not clear and no identifiable risk factors have been demonstrated thus far for solitary schwannomas however schwannomas may be seen in the autosomal dominant neurofibromatosis type 2 alongside at least one other nervous system tumour such as an acoustic neuroma, meningioma and glioma [4]. A facial nerve schwannoma (FNS) can occur at any point along its course from the cerebello--pontine angle to its peripheral branches [5]. In a review of 700 parotidectomies, Nussbaum observed only 1 case of FNS [6].…”
Section: Introductionmentioning
confidence: 99%
“…In type C tumors, the main trunk of the facial nerve is resected while in type D, the main trunk and at least one of the temporofacial or cervicofacial branches is also removed. 11 The goal of the treatment is to remove the tumor with preservation of the facial nerve but frequently it is not possible to preserve the nerve. The management of intraparotid schwannoma depends on extent of facial nerve dysfunction, localization of tumor to parotid gland and Intratemporal extension.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al overcame this difficulty by employing intra--operative frozen section studies to reach the correct diagnosis [26]. On the one hand, frozen section examination that has been performed intra--operatively is recommended for both diagnosis and exclusion of malignancy [5,27]. On the other hand, occasionally the schwannoma is mistaken for a fibrosarcoma leading to unwarranted radical surgery [28].…”
Section: Discussionmentioning
confidence: 99%